The spherical distance for intuitionistic fuzzy sets and its application in decision analysis - Gong, Zaiwu; Xu, Xiaoxia; Yang, Yingjie; Zhou, Yi; Zhang, Huanhuan (Technological and Economic Development of Economy, 2016)
Different from traditional distances between Intuitionistic Fuzzy Sets (IFS), the spherical distance between two IFSs relies not only on their relative differences but also their absolute values. In this paper, we generalize the properties of spherical distance measures between IFSs, and investigate the applications of spherical distance measures in group decision making, pattern recognition and medical diagnosis. We develop an optimization spherical distance model with IFS preference in group decision making, and demonstrate that this model is feasible and practical with an evaluation model of drought risk. By using comparative analysis method, we show that this new spherical distance can also be applied in other fields such as pattern recognition and medical diagnosis.